Genome-wide identification and evolution of the RCP gene family in soybean uncovers stress-responsive candidates - Xiaoli Guan; Run Yuan; Ao Shen; Yanhong Wang; Yuanmeng Yu; Liying Zou; Yuming Yang; Jinyu Zhang; Zhongwen Huang; Li Wang (Functional & Integrative Genomics, 2026)

Cross domain fault diagnosis of small modular reactor using sample synthesis and transfer learning with attention mechanism - Run Luo; Xiangcheng Pan; Yadong Li; Yang Liu; Hongtao Wan; Shun Hu; Tao Yu; Chao Xie (Annals of Nuclear Energy, 2026)

Safety, immunogenicity, and broad-spectrum protective efficacy of a naturally attenuated GCRV-II strain against viral and bacterial challenges in grass carp - Dingzhe Zou; Yifei Li; Jie Zhou; Wangqian Xu; Ying Tian; Run Yang; Yujie Gu; Xiangyu Tian; Yucheng Lin; Jiping Zhang; Weiwei Zeng (Fish & Shellfish Immunology, 2026)

Revealing the dominant role of pectin in softening texture and enhancing drying behaviors of grapes after cold plasma pretreatment - An-An Zhang; Fan Yang; Ming-Qiang Xu; Wei-Peng Zhang; Jin-Run Li; Hai-Bin Yang; Jing-Shou Zhang; Wei-Qiao Lv; Hong-Wei Xiao (Food Research International, 2026)

Valorization of coffee Silverskin into a novel dietary Fiber ingredient: A comprehensive study on structure, and in vitro/in vivo antioxidant activity - Chen Dai; Run Tang; Ziyu Guo; Weixing Yang; Xiaoyu Gao; Jun Sheng; Yang Tian; Jia Liu (Food Research International, 2026)

Structural features of endogenous polyphenols in modulating oxidative stability of tiger nut (Cyperus esculentus L.) oil: Insights from Rancimat and density functional theory - Zheng-Kai Zhang; Meng-Chen Xie; Jun-Chao Zhang; Lu-Han Sun; Xiao-Shuang Cai; Run-Yang Zhang; Guo-Qiang Zhang; Hua-Min Liu (Food Chemistry, 2026)

Asymmetric microbial community reassembly under 7-year experimental precipitation decouples soil carbon storage in a coastal wetland - Run Dang; Leilei Xiao; Lifeng Zhou; Jian Liu; Zhenghao Liang; Yan Wang; Weimin Song; Xiaojie Wang; Xiaojing Chu; Xiaoshuai Zhang; Yang Song; Wanlin Song; et al. (Environmental Research, 2026)

Impact of urban functional zoning on carbon emission from electricity consumption: a multi-source data integration approach on Xuzhou China - Jiawei Xiang; Jia Wang; Hui Yang; Liu Cui; Yina Qiao; Run Cai; Shuzhen Wu; Yuan Zhang (Energy and Buildings, 2026)

The lnc40545-miR-965-CYP307A1 regulation pathway mediates imidacloprid resistance in Rhopalosiphum padi (L.) - Yong-Po Lv; Ren-Jie Li; Yu-Tai Jiang; Bai-Zhong Zhang; Yu-Yang Peng; Yong Sun; Dong-Mei Chen; Fan-Bin Kong; Run-Qiang Liu; Hai-Hong Gu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Delta-Band Dynamics of CaMKI-Positive Preoptic Neurons Encode Thermal Homeostatic Information - Dian-Dian Wang; Run-Zhou Yang; Song-Tang Sun; Ya-Lun Sun; Rui-Yu Wang; Xiao-Yan Meng; Sen-Miao Li; Jia-Kang Li; Pei-Pei Liu; Shu-Ang Li; Jian-Sheng Kang (Neuroscience Bulletin, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Study on the influence depth for vertical bearing capacity of bucket foundations in layered clay using lower-bound limit analysis - Can Yang; Run Liu; Guang Si Chen (Ocean Engineering, 2026)

Climatic drying-wetting cycles induced dynamic coupling effect between 3D soil desiccation cracking and moisture redistribution - Yu-Xuan Chen; Jun-Zheng Zhang; Chao-Sheng Tang; Run-Yang Lan; Qing Cheng; Jin-jian Xu; Ben-Gang Tian (Journal of Hydrology, 2026)

RDO3 REPRESSOR 27, a new MED25 allele, regulates seed dormancy dependent on DOG1 and ABA pathways in Arabidopsis - Yue Yang; Xiao-Ying Li; Run Ding; Hong Cao; Yongxiu Liu; Yu Li (Planta, 2026)

A subset of endogenous P2X5 transcripts encodes ATP-sensitive receptor isoforms - Xiao-Na Yang; Dong-Ping Wang; Chen-Hui Shen; Xi Chen; Ai-Xin Zhang; Meng Zhang; Xing Zhou; Yun Tian; Peng Cao; Michael X. Zhu; Hui Yang; Chang-Run Guo; et al. (Science Bulletin, 2026)

Impacts of extreme drought events on forest ecosystem resilience in mainland Southeast Asia - Lusha Ma; Kun Yang; Zongqi Peng; Run Sun; Mingfeng Zhang; Danni Su; Jingcong Ma; Yanhui Zhu; Xianchun Pan (Science Bulletin, 2026)

Extent of soil disturbance and spatial strength degradation induced by spudcan penetration and extraction in clay - Cheng-feng Li; Rui Zhou; Run Liu; Hai-yang Zhang; Peng-cheng Ma (Ocean Engineering, 2026)

ClO₂-induced VBNC state in Enterococcus faecalis poses a health risk in drinking water systems - Ziyi Zhang; Shuai Cheng; Menghua Duan; Yihong Wang; Weipeng Xu; Yiming Lu; Hui Yang; Na Lv; Run Ma; Jiahui Guo; Chao Shi (Journal of Hazardous Materials, 2026)

Characteristics of the radar bright band observed over a high-altitude lake - Run Han; Yingying Chen; Xiaoyan Ling; Kun Yang; Xin Li; Junbo Wang; Changhui Zhan; Xu Zhou; Ming Chen (Atmospheric Research, 2026)

A comprehensive review on the chemical composition, pharmacological effects and quality evaluation of Gentiana straminea Maxim. - Yuan-Wen Zhuang; Min Wang; Jian-Tao Zhao; Yu-Qing Wang; Run-Qian Yu; Huan Xia; Xiao-Hong Wei; Peng-Cheng Lin; Gui-Yang Xia; Sheng Lin (Journal of Natural Medicines, 2026)

Hirsutanines H−O, monoterpene indole alkaloids from Uncaria hirsuta with neuroprotective effects - Nan An; Lei-Ming Wu; Shu-Qi Wu; Jia-Luo Huang; Dong Huang; Fang-Yu Yuan; Yi-Ling Liao; Run-Zhu Fan; Xian-Yuan Yang; Gui-Hua Tang; Lu Gan; Sheng Yin (Phytochemistry, 2026)

Enhancing camptothecin biosynthesis in Camptotheca acuminata through CrLAMT transfer from Catharanthus roseus - Ru Huang; Wen-Hui Ma; Bing-Run Yang; Fang Yu; Ping Kou (Biotechnology Letters, 2026)

First isolation and identification of a rhabdovirus from bluegill sunfish (Lepomis macrochirus) - Haiyue Chen; Wangqian Xu; Dingzhe Zou; Baozhou Wu; Shuguang Hao; Huajia Yao; Jie Zhou; Ying Tian; Yifei Li; Run Yang; Yujie Gu; Yu Liu; et al. (Aquaculture, 2026)

Uncertainty quantification and physical information learning for safe measurement of resonant flowmeters in multiphase flow: A Bayesian approach with physically-constrained residual injection - Ziwei Yang; Haibo Liang; Run Jiang; Mingyang Liu; Deshen Li; Jie Liu; Jingwen Hu (Process Safety and Environmental Protection, 2026)

Investigation of soot formation characteristics in C2H4 / NH3 laminar diffusion flames: Effects of different gradient blending ratios of NH3 - Jiahao Wang; Run Hong; Yuhang Yang; Yutao Zhang; Huaqiang Chu (Fuel, 2026)

Reconstructing the spatiotemporal distribution of microbial-induced carbonate precipitation using electrical conductivity tomography - Jun-Zheng Zhang; Chao-Sheng Tang; André Revil; Chao Lv; Jin-Jian Xu; Run-Yang Lan; Qi-You Zhou (Engineering Geology, 2026)

Molecular epidemiology reveals co-circulation of five Anaplasma species with zoonotic potential in sheep and goats from Henan province, China - Jia-Run Yang; Wei-Hao Tan; Jie-Yue Liang; Jing-Rong Li; Yu-Ru Cao; Wan-Yu Li; Jian-Wei Shao (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

Co-assembled organic phosphorescent crystals with ultralong phosphorescence in high-temperature and water environment - Bin Li; Ziyi Lu; Wensheng Xu; Run Wang; Jiang Liu; Linshuo Jiang; Yin Xiao; Jianchao Ma; Yang Li; Xilong Yan; Bowei Wang; Ligong Chen (Chemical Engineering Journal, 2026)

Defect-passivated Te-doped Cs2HfCl6 perovskite microcrystals with high efficiency and robust stability for X-ray imaging - Yanqing Zu; Run Gan; Lixia Jing; Bing Yang; Binglin Zeng; Liru Yuan; Peitao Liu; Xiaodong Li; Ailing Feng; Lei Zhou (Chemical Engineering Journal, 2026)

From species to therapeutic property: distribution differences of threatened Chinese medicinal plants under climate change - Yun-Han Chen; Rui Yang; Run-Han Jiang; Yu Xia; Ling-Feng Mao (Biodiversity and Conservation, 2026)

Tissue Tropism and Pathogenesis of LMBV in Largemouth Bass: A Comparative Study of Injection and Immersion Infection Models - Tianmei Hu; Dingzhe Zou; Baozhou Wu; Haiyue Chen; Shuguang Hao; Ying Tian; Wangqian Xu; Yifei Li; Jie Zhou; Run Yang; Jiping Zhang; Yu Liu; et al. (Journal of Fish Diseases, 2026)
Largemouth bass ranavirus (LMBV) poses a significant threat to the aquaculture industry by causing severe systemic disease and substantial economic losses. This study investigates the tissue distribution, pathological damage, and host response following LMBV‐GD1909 infection using two infection models: experimental injection and simulated natural immersion. In the injection model, infected fish exhibited clinical signs, including skin ulcers, haemorrhaging at fin bases, body darkening and organ swelling. Histopathological analysis revealed extensive multi‐organ damage, particularly in the liver, spleen, and kidney, characterised by necrosis, haemorrhage, vacuolar degeneration and inflammatory infiltration. Haematological and serum biochemical analyses indicated significant alterations in key parameters, including elevated WBC, RBC and GLU levels, and reduced PLT, TP and LDH levels, reflecting systemic physiological disruption. Viral dynamics analysis demonstrated the pantropic nature of LMBV, with rapid dissemination to multiple tissues post‐injection. The liver and spleen were identified as primary target organs, showing the highest viral loads and most severe pathology, indicating a direct correlation between viral load and organ dysfunction. In the immersion model, simulating natural infection, the gills and skin displayed the highest viral loads initially, identifying them as the major entry portals. The gills also served as a key site for viral replication, with a clear gradient of viral spread from external to internal tissues observed over time. This study comprehensively elucidates the tissue tropism, dissemination pathways, and pathological impact of LMBV, providing critical insights for developing targeted prevention and control strategies against LMBV.

Deformation behavior of saturated sandy soil under offshore wind bucket-shaped foundation ultimate overburden conditions - Zhipeng Cao; Xiaolei Wang; Yang Wu; Jim Shiau; Libo Liu; Run Liu; Liteng Liu; Jindou Cai (Marine Georesources & Geotechnology, 2026)

Coordinated EISCAT and all-sky imager observations of dayside aurora effects on polar cap patch vertical properties - Zhiwei Wang; Desheng Han; Huixuan Qiu; Yong Wang; Huigen Yang; Jian Zhang; Jianjun Liu; Xiangcai Chen; Qiang Zhang; Su Zhou; Run Shi (Science China Earth Sciences, 2026)

DrPISA: Deep eutectic solvent-assisted reverse proteome-integrated solubility alteration for high-sensitivity drug target identification - Liu Yang; Tian-Bo Ma; Chen-Wan Guo; Run-Bo Yu; Ping Li; Hua Yang; Wen Gao (Analytica Chimica Acta, 2026)

Microbial Responses to Warming Reduce Deep Blue Carbon Storage - Leilei Xiao; Jian Liu; Genevieve L. Noyce; Jaehyun Lee; Carlos M. Duarte; Meng Zhou; Min Luo; Ruifeng Sun; Run Dang; Lifeng Zhou; Lirong Zhang; Chuancheng Fu; et al. (Global Change Biology, 2026)
Coastal wetlands are critical blue carbon reservoirs, yet the depth‐resolved impacts of warming on belowground carbon dynamics remain poorly understood. Over the course of an 8‐year in situ experiment, we investigated plant‐derived carbon inputs, soil carbon losses via respiration, and microbially mediated carbon fixation across a 60 cm soil profile under a projected 2°C atmospheric warming scenario. Plant carbon fixation (above‐ and belowground net primary productivity) and soil respiration exhibited synchronized responses to warming, with an initial increase, followed by a decline in the mid‐term, and no significant response in the later stages. Soil and microbial respiration stabilized after prolonged exposure to elevated temperatures, as these processes were constrained by substrate availability. In contrast, phospholipid fatty acid profiling, amino sugar biomarkers, and metagenome‐assembled genomes consistently indicated a greater than one‐third reduction in microbial carbon fixation within subsoils (40–60 cm). Our fully factorial, depth‐stratified warming design reveals the particular vulnerability of deep soil microbial carbon retention to long‐term climate warming, independent of shifts in plant input or respiratory carbon loss. This work highlights underappreciated pathways influencing soil blue carbon dynamics in a changing world.

Transcriptomic profiling reveals that NSDV exploits autophagy as a proviral mechanism to enhance viral replication - Xue-Lian Zhang; Xiao-Wen Li; Wei-Hao Tan; Jia-Run Yang; Jie-Yue Liang; Jian-Wei Shao (Veterinary Microbiology, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

Expansion of cluster 3 Tembusu virus in Guangdong geese with hepatitis-splenomegaly syndrome and evidence of recombination - Chen-Chen Yang; Wei-Hao Tan; Run-Jie Zou; Ying Liang; Xue-Lian Zhang; Jian-Wei Shao (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

Failure Behavior and Energy Evolution of Granite Containing Pre-existing Fissures Characterized by AE and DIC - Run-ze Zhang; Chuan-xin Rong; Bin Wang; Hua-qiao Xu; Yan-zhe Li; Yang Wang (Applied Geophysics, 2026)

Whole-genome sequencing reveals the genetic diversity of Aeromonas from freshwater fish and the presence of novel genomic islands carrying clinically important antimicrobial resistance genes - Xiao-Qin Wang; Ke Wu; Run-Min Kang; Heng Lin; Lu-Ya Liu; Ting Xian; Yi-Zhi Tang; Xin Yang; An-Yun Zhang; Hong-Ning Wang; Chang-Wei Lei (Aquaculture, 2026)

An unprecedented alternariol-zinnol hybrid and six undescribed zinnol derivatives from the phytopathogen Alternaria solani and their cytotoxic activities - Ming Hu; Run-Cheng Yan; Qiao-Ling Wei; Jiang-Li Su; Bi-Juan Yang; Wen-Chao Tu; Gan-Peng Li; Xing-De Wu (Phytochemistry, 2026)

Unraveling the catalytic/adsorptive roles of powdered activated carbon in iodide removal by Mn(VII) oxidation - Run Huang; Chaoting Guan; Juan Li; Yi Yang; Yongze Liu; Jin Jiang (Journal of Hazardous Materials, 2026)

Numerical investigation on combustion behavior of an X-type rotary engine: Impact of hydrogen enrichment and engine speed - Run Zou; Lei Zhang; Ting Hou; Yanhong Zhou; Wei Yang; Lijun Lei; Feng Li (Fuel, 2026)

Effect of different long-chain oxygenated fuels on the nanostructure and physico-chemical properties of soot in n-heptane flames: An experimental comparative study - Yuhang Yang; Jiahao Wang; Run Hong; Bingbing Qiu; Huaqiang Chu (Fuel, 2026)

Structural characterization and prebiotic activity of oligosaccharides derived from sesame meal produced by different oil extraction methods - Hui-Fang Duan; Xiao-Rong Chen; Ran Zhang; Yuan-Qing Luo; Chang-Yong Lu; Ke-Qing Liu; Rui-Fu Cui; Run-Yang Zhang; Hua-Min Liu (Food Research International, 2026)

Chitosan/gelatin-based film activated by Pickering emulsion of citrus essential oil stabilized by esterified starch/whey protein isolate fibrils: Application in preserving freshness of blueberry - Run Ji; Hao Guo; Xu Yang; Lepei Wang; Xiuling Zhang; Hui Zhang (Food Chemistry, 2026)

Selection of catalysts in the synthesis of carbon nanotubes by flame method and their application: Status and challenges - Huaqiang Chu; Hui Zhou; Run Hong; Yuhang Yang; Xing Zhang; Hanfang Zhang (Fuel, 2026)

miR-23a modulates chlorantraniliprole susceptibility by targeting SfGSTs3 in Spodoptera frugiperda (Smith) - Fan-Bin Kong; Yong-Po Lv; Bai-Zhong Zhang; Meng-Yuan Zhang; Ling-Ling Cui; Ren-Jie Li; Dong-Mei Chen; Yu-Yang Peng; Run-Qiang Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Therapy-chemotherapy dual mode intelligent nano hydrogen generator for tumor treatment - Xuheng Chen; Hongxin Zhang; Yong Liu; Feiyu Zhao; Bowen Li; Run Yang; Niansong Qian; Yang Bai; Liang Zhao; Bin Zheng; Shanlong Zhang (Chemical Engineering Journal, 2026)

Biomass growth, nutrient removal, and microbial community dynamics in mono-, Co-, and sequential culture of screened cyanobacteria with microalgae for dairy wastewater treatment - Khin Khin Phyu; Suli Zhi; Junfeng Liang; Zengjun Yang; Run Zhao; Jiahua Liu; Yuang Cao; Han Wang; Keqiang Zhang (Bioresource Technology, 2026)

A unified intracellular pH landscape with SITE-pHorin: a quantum-entanglement-enhanced pH probe - Shu-Ang Li; Xiao-Yan Meng; Su Zhang; Ying-Jie Zhang; Run-Zhou Yang; Dian-Dian Wang; Yang Yang; Pei-Pei Liu; Jian-Sheng Kang (Science China Life Sciences, 2026)

Cloning, heterologus expression and characterization of a thermophilic and salt tolerant GH11 xylanase from Allostreptomyces psammosilenae YIM DR4008T - Xin-Wei Li; Dan Zhu; Lei Li; Run-Feng Yang; Shi-Yuan Fan; Zhi-Hua Lv; Meng-Di Rao; Rong-Huang Song; Peng Sang; Yi-Rui Yin; Li-Quan Yang (Antonie van Leeuwenhoek, 2026)

Identification of lncRNAs Associated with Imidacloprid Resistance in the Grain Aphid Rhopalosiphum padi (L.) (Hemiptera: Aphididae) - Ling-Ling Cui; Yong-Po Lv; Ren-Jie Li; Yu-Tai Jiang; Bai-Zhong Zhang; Yu-Yang Peng; Jin-Song Zheng; Fan-Bin Kong; Run-Qiang Liu (Neotropical Entomology, 2025)

Target Fibroblast-B cell crosstalk via MIF signaling drives pathogenic B cell differentiation and joint damage in knee osteoarthritis - Bizhi Tu; Zheng Zhu; Yan Li; Zhengming Zhu; Shijie Wang; Peizhi Lu; Ya Li; Shuo Yang; Dingtao Hu; Run Fang; Rende Ning (Inflammation Research, 2025)

Decaprenyl diphosphate synthases in Monolepta hieroglyphica: DPPS-mediated CoQ biosynthesis impacts juvenile hormone and gut microbiota - Xuan Song; Jun-feng Kou; Chang Liu; Yong Yang; Da-wei Zhang; Chao-qun Yi; Wen-tao Liu; Run Chen; Wei-hao Guo; Yue-qin Wang; Tian-tao Zhang; Yong-jun Zhang (Insect Biochemistry and Molecular Biology, 2025)

Drinking water quality criteria value estimation for representative haloacetamide disinfection byproducts via a benchmark dose approach based on an association analysis between drinking water exposure and altered liver function in a community population in Wuxi from Jiangsu province - Shunan Wang; Jingying Zhu; Wanjun Zhang; Chao Yang; Lingling Xu; Limei Chen; Yao Li; Run Zhou; Xinliang Ding (Environmental Pollution, 2025)

High-precision geochronology of the Early Cretaceous Jiufotang Formation: Temporal constraints on the late phase of the Jehol Biota - Yu-Ting Zhong; Magdalena H. Huyskens; Run-Jian Chu; Han-Qing Yang; Jian-Fang Hu; Ya-Qiong Wang; Shi-Xi Cai; Qiong Wu; Qiang Ma; Huai-Chun Wu; Qing-Zhu Yin; Yi-Gang Xu (Earth and Planetary Science Letters, 2025)

A study on soil erodibility and the applicability of estimation methods in Robinia pseudoacacia L. mixed forests on the Loess Plateau, China - Jin-long Ma; Bing Wang; Run-hao Yu; Yan-fen Yang; Guo-bin Liu; Jing Wang; Cheng-fang Li (CATENA, 2025)

Enhancement of polyethylene biodegradation by high-performance bacterial isolates - Hong Zhang; Fan Yang; Mengzong Hou; Run Hu; Lisha Song; Qiang Liu; Yanjiao Qi; Juanli Liu (Journal of Soils and Sediments, 2025)

Frititaipaines A−O, undescribed cevanine-type isosteroidal alkaloids from the bulbs of Fritillaria taipaiensis and their anti-neuroinflammatory and AChE inhibitory activities - Zai-Long Huang; En-Ke Qu; Lan-Run Yang; Rui Luo; Yan-Ni Liang; Shi-Jun Liu; Yuan-Zhen Xu; Dong-Bo Zhang (Phytochemistry, 2025)

Dual-gripper coordination effect stabilizing zinc anodes for high-performance zinc metal batteries - Tian-Yi Yang; Kun Li; Ting-Ting Su; Li Ma; Qiu-Shuai Xu; Chang-You Shao; Wen-Feng Ren; Run-Cang Sun (Chemical Engineering Journal, 2025)

Environmental adaptive nanoplatform for bacteriotherapy - Wei Sun; Yang Bai; Xuefei Shao; Bowen Li; Haohua Yuan; Xuheng Chen; Run Yang; Yuan Liu; Shixiang Cheng; Yanguo Xi; Qing-hui Meng; Bin Zheng; et al. (Chemical Engineering Journal, 2025)

Waste biomass-derived organic matter for sustainable soil remediation: Enhancing heavy metal removal and eluent reuse in agricultural application - Shuai Yang; Chen Tu; Guo-ming Liu; Yuan Li; Yi Wang; Xia Zhu; Shao-cheng Si; Run-lai Luo; Zhong-yuan Li; Yong-ming Luo (Bioresource Technology, 2025)

Construction and optimization of a near-infrared spectroscopic model for the assessment of nitrogen and phosphorus in dairy farm slurry under different temperatures - Mengting Li; Shengbo Liu; Di Sun; Zengjun Yang; Run Zhao; Keqiang Zhang (Computers and Electronics in Agriculture, 2025)

Antibiotic resistance genes in multi-matrices of Chaohu Lake: Spatiotemporal variation and correlation with pesticides and PPCPs - Hao Yang; Hongwei Fu; Yutong Zhao; Run Li; Man Cao; Yi Liu; Yachao Ni; Wei Song; Yangyang Liang; Panyuan Cai; Wei Chang; Fangbiao Tao; et al. (Journal of Hazardous Materials, 2025)

Enzyme treatment combined with Maillard reaction modification of sunflower meal hydrolysates to prepare sunflower seed oil flavor enhancer - Shuai Xu; Qing Guo; Yu-Xuan Jin; Run-Yang Zhang; Hua-Min Liu; Zhao Qin; Xiu-Zhu Yu; Xue-De Wang (Food Chemistry, 2025)

Molecular docking screening of endogenous protease inhibitors in sea bass (Lates calcarifer) and in vitro validation of their inhibitory efficacy - Run-Jian Gao; Lu Sun; Sen-Di Zhou; Yu-Meng Liu; Wei-Qiang Qiu; Sheng-Ping Yang; Yun-Fang Qian (Food Bioscience, 2025)

Bioinspired moist-electric generator with self-protection and autonomous healing enabled by dynamic supramolecular polyurethane - Renquan Xing; Ying Sun; Xiangyi Hou; Jing Yan; Run Wang; Xupin Zhuang; Guang Yang (Chemical Engineering Journal, 2025)

Harnessing built-in electric fields for enhanced electron transfer in biosensor for precise digital health assessment - Tian-Run Lv; Yaqiong Yang; Jia-Chen Zhang; Ling Qi; Ming-Jie Yin; Yong Li; Ken Tye Yong; Quan-Fu An (Chemical Engineering Journal, 2025)

Terrestrial–aquatic microbial community coalescence slows litter decomposition in forest streams - Han Jiang; Yinghui Yang; Jiawen Liang; Run Liu; Yueting Pan; Tingting Cao; Siyuan Chen; Zunian Ran; Chang Zhao; Yanli Tian; Xingjun Tian (Plant and Soil, 2025)

Factors contributing to high oxidative stability in oil from long-term stored tiger nut (Cyperus esculentus L.): Endogenous components - Jia-Ke Li; Deng-Ju Cai; Hang-Yu Zhao; Yu-Xiang Ma; Xiao-Shuang Cai; Hua-Min Liu; Run-Yang Zhang (Journal of Stored Products Research, 2025)

Evolution mechanism of catalytic performance in piezo-photocatalytic recycled pervious concrete during hydration to carbonation - Hailiang Fei; Guanyu Liu; Jiayu Wu; Jiaxu Zhang; Yulong Zheng; Mingtao Run; Fen Li; Sanqiang Yang (Chemical Engineering Journal, 2025)

Post-dynamic behaviors of the saturated loess in the Zhongchuan slide triggered by the Jishishan M6.2 earthquake - Haiping Ma; Keliang Ren; Wenguo Ma; Youzhen Yang; Chen Li; Run Cai (Natural Hazards, 2025)

Strong heterogeneity in laterally exchanged particulate organic matter across tidal marshes in a large river delta - Qi Wu; Hong-Sheng Cao; Youhei Yamashita; Christian Lønborg; Run Li; Jianzhong Ge; Hualei Yang; Bolin Liu; Jinzhou Du; Fang Cao (Environmental Research, 2025)

Piezo-photocatalytic NO degradation performance and load-light coupling mechanism of g-C3N4/BaTiO3 fog seal pavements - Guanyu Liu; Tianzheng Zhao; Jiayu Wu; Yaobin Zhan; Meicheng Kuang; Mingtao Run; Fen Li; Sanqiang Yang (Chemical Engineering Journal, 2025)

Identification and functional analysis of BAG gene family contributing to verticillium wilt resistance in upland cotton - Zhijuan Hu; Jingjie Yuan; Run Zou; Yilan Wang; Xuan Peng; Xingyong Yang; Chengjian Xie (Plant Science, 2025)

Preparation and characterization of highly stable pH-sensitive multifunctional films based on co-pigment-anthocyanin conjugate system for pork monitoring and preservation - Shuang Song; Run Ji; Jieli Xu; Xiyue Yang; Qiyun An; Xiuling Zhang; Wentao Zhang (Food Hydrocolloids, 2025)

Bioinspired hydrogel tactile sensor via pressure-intensified ion signals with self-healing and anti-frozen capability - Yi-Han Xue; Tian-Run Lv; Huiting Zhang; Ya-Qiong Yang; Ming-Jie Yin; Quan-Fu An (Chemical Engineering Journal, 2025)

Identification and comparative analysis of flowering genes in the Sugar pathway from five Gossypium species - Lei-Ming Liu; Chuan-Bo Jiang; Yi-Lin Yang; Tian-Run Mei; Ruo-Fei Liu; Hai-Liang Liu; Xian-Zhong Huang (Plant Gene, 2025)

Restoration of secondary forest in the Greater Mekong Subregion struggles to offset primary forest carbon losses - Zongqi Peng; Yanhui Zhu; Kun Yang; Yi Luo; Xixi Lu; Jiasheng Wang; Yang Zhang; Danni Su; Run Sun; Mingfeng Zhang; Jingcong Ma; Yang Liu; et al. (Global and Planetary Change, 2025)

The association between greenspace exposure and sperm quality: A retrospective cohort study focusing on sperm kinematics and the influence of buffer settings - Sixuan Zeng; Tingting Yang; Run Tian; Xin Jin; Lu Zhang; Fuping Li; Leyao Fu; Jiarui Cai; Junhao Liao; Guishuang Song; Xiaoli Luo; Yujue Wang; et al. (Environmental Research, 2025)

Positive Dose–Response Relationship Between Urinary Trihalomethanes and Blood Pressure in Adults in Wuxi, China - Shunan Wang; Qianqian Wang; Chao Yang; Li Yang; Lingling Xu; Run Zhou; Limei Chen; Yao Li; Pengfei Zhu; Xinliang Ding (Exposure and Health, 2025)

Physiological, transcriptomic and metabolomic responses of the marine diatom Phaeodactylum tricornutum to the auxin IAA - Yu-Ting Chen; Dong-Sheng Zhao; Xiao-Li Liu; Huan Yang; Run-Ze Gu; Nan Li; Xiufeng Yan; Hui-Xi Zou (Algal Research, 2025)

Enhancing fruit quality through unraveling the molecular and physiological basis and preventing cracking in jujube (Ziziphus jujuba Mill.) - Hong-Xiang Zhou; Run-Zhe Wang; Wen-Ting Luo; Yang Liang; Shi-Yu Liu; Juan Chen; Ji-Qing Peng; Yan-Xia Fan; Shu-Zhan Li; Chuan Guo; Zi-Qiang Zhang; Feng-Xia Shao; et al. (Postharvest Biology and Technology, 2025)

Whole rock and zircon geochemistry of the Tieshan pluton in Daye region, Eastern China: Implication for petrogenesis and Fe-Cu-Au-(Co) mineralization - Bao Zhou; Guang Wen; Run-Jie Zhou; Yue Sun; Chang-Xiong Wu; Jin Zhu; Zhi-Jun Qin; Xiao-Yang Liu; Xiao-Zeng Cheng (Journal of Geochemical Exploration, 2025)

Heterotrophic nitrification-aerobic denitrification strains: An overlooked microbial interaction nexus in the anaerobic-swing-anoxic-oxic (ASAO) plug-flow system - Run-Ze Xu; Jia-Shun Cao; Song Cheng; Jing-Yang Luo; Bing-Jie Ni; Fang Fang; Weijing Liu; Peifang Wang (Journal of Environmental Management, 2025)

Characterization of β-cyclodextrin inclusion complexes embedded with lemongrass and basil essential oils and their modified sustained-release pads for large yellow croaker (Larimichthys crocea) fillet preservation - Yun-Fang Qian; Cheng-Jian Shi; Lu Sun; Run-Jian Gao; Sheng-Ping Yang (Food Bioscience, 2025)

MXene-enabled gas sensors for wearable breath monitoring - Run Yuan; Yixuan Yang; Bingsuo Zou; Yabin Zhang (Chemical Engineering Journal, 2025)

Endophytes and soil microorganisms participate in the germination of Sinojackia xylocarpa Hu by degrading the pericarp - Zi-Hao Li; Xin-Yi Ma; Huan Yang; Run-Guo Zang; Jia-Ru Li (Acta Physiologiae Plantarum, 2025)

Optimized design method for power matching of composite hydrodynamic wind turbine based on wind farm data mining - Yingzhe Kan; Wei Jiang; Min Yang; Run Qian; Wanyu Wang (Ocean Engineering, 2025)

Layer-by-layer nanoencapsulation strategies for enhanced oral delivery and function of Lactobacillus plantarum B2 - Yun-Yang Zhu; Run-Hui Ma; Kiran Thakur; Wang-Wei Zhang; Jian-Guo Zhang; Mohammad Rizwan Khan; Chenzhong Liao; Zhao-Jun Wei (Food Hydrocolloids, 2025)

Enhanced regeneration of large segmental bone defects via hierarchically structured bioactive scaffolds - Mo-Han Wang; Shao-Meng Wen; Yun-Hong Cong; Huai-Ling Gao; Xian-Yu Zheng; Zi-Xiang Han; Run Wang; Rui Xu; Lu Yang; Wen-Jing Li; Zhao Pan; Jia-Cai He; et al. (Chemical Engineering Journal, 2025)

Boosting structural stability and air stability towards layered oxide cathodes for potassium ion batteries - Hong Chen; Lu-Kang Zhao; Xuejiao Cheng; Xuan-Wen Gao; Zhaomeng Liu; She-Dong Li; Dong-Run Yang; Tian-Zhen Ren; Wen-Bin Luo (Chemical Engineering Journal, 2025)

Methane production related to microbiota in dairy cattle feces - Jian Liu; Meng Zhou; Lifeng Zhou; Run Dang; Leilei Xiao; Yang Tan; Meng Li; Jiafeng Yu; Peng Zhang; Marcela Hernández; Eric Lichtfouse (Environmental Research, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

From metabolomics to therapeutics: identifying causal metabolites and potential drugs for the treatment of osteoarthritis - Heng Li; Jingyan Sun; Jiewen Zhang; Yang Chen; Yiwei Zhao; Ruomu Cao; Ning Kong; Xudong Duan; Huanshuai Guan; Run Tian; Kunzheng Wang; Pei Yang (Inflammopharmacology, 2025)

Investigating spatial-temporal characteristics of joint activity/travel behaviour with smart card data - Chen Yang; Xiao Fu; Run Dong (Travel Behaviour and Society, 2025)

Enhanced effect of ferrous sulfate on nitrogen retention and PBAT degradation during co-composting by combing with biochar-loaded FN1 bacterial composites - Long Cao; Linshan Wang; Yanjiao Qi; Shen Yang; Jiazhi Gao; Qiang Liu; Lisha Song; Run Hu; Zifan Wang; Hong Zhang (Journal of Environmental Management, 2025)

Effect of ignition timing on combustion characteristics and emissions of an X-type rotary engine with the high efficiency hybrid cycle - Run Zou; Feng Li; Jinxiang Liu; Wei Yang; Lijun Lei; Lei Zhang (Fuel, 2025)

The link between eye movements and cognitive function in mild to moderate Alzheimer’s disease - Xiao-ting Ma; Lin-lin Yao; Shan-wen Liu; Xiao-fen Weng; Run-ying Bao; Yi-fan Yang; Yi-feng Li; Yan-yun Sun; Dan Xu; Zhen-yu Jia; Hua Hu (Experimental Brain Research, 2025)

Understanding nitrogen removal and N2O emission mechanisms in an anaerobic-swing-anoxic-oxic (ASAO) continuous plug-flow system for low C/N municipal wastewater - Run-Ze Xu; Jia-Shun Cao; Jing-Yang Luo; Bing-Jie Ni; Fang Fang; Weijing Liu; Peifang Wang (Science of The Total Environment, 2024)

Sustainable utilization of phosphorus-rich sludge in cement composites: Multiscale evaluation and mechanistic analysis - Shengli Ren; Zhirong Xu; Benqin Yang; Xiao-Yong Wang; Yi Han; Run-Sheng Lin; Yongpang Liao (Journal of Environmental Chemical Engineering, 2024)

Undrained Capacity of a Bucket Foundation with a Limited-Tension Interface for Offshore Wind Turbines - Jiayu Wang; Bin Li; Run Liu; Xu Yang; Chao Liang (Journal of Ocean University of China, 2024)

Study on the thermo-hydraulic behaviors within a CiADS 61-pin wire-wrapped fuel assembly under porous blockage conditions based on LBEblockageFoam - Yun-Xiang Li; Run-Sheng Yang; Yue Li; Xing-Kang Su; Yi-Wen Han; Zi-Nan Huang; Lu Meng; Song Li; You-Peng Zhang; Lu Zhang; Wei Jiang (Annals of Nuclear Energy, 2024)

Ecological risk assessment methods for oxidative by–products in the oxidation degradation process of emerging pollutants: A review - Yufei Yang; Zhi-Hui Xie; Hao Wang; Shu-Run Yang; Tingting Wang; Chuan-Shu He; Bo Lai (Science of The Total Environment, 2024)

A new framework for assessing and dealing with heat risk from an urban resilience perspective - Teng Zhang; Yixuan Sun; Run Wang; Yong Yang; Le Yin; Liangang Li; Baolei Zhang (Journal of Cleaner Production, 2024)

Oxygen atom activated ZIF-67/carbon cloth in plasma system for CO2 reduction - Yi Zhang; Yiping Shen; Mengru Shan; Man Wang; Run Wang; Shiying Yang; Sihao Jiang; Yanqing Cong; Boqiong Jiang (Journal of Environmental Management, 2024)

The potential of glycinin basic peptide derived from soybean as a promising candidate for the natural food additive and preservative: A review - Hou-Qi Ning; Hai-Run Fan; Chun-Ling Yang; Gui-Jin Sun; Ying-Qiu Li; Hai-Zhen Mo (Food Chemistry, 2024)

Evidence of polybrominated diphenyl ethers (PBDEs) and alternative halogenated flame retardants (AHFRs) in wild fish species from the remote tropical marine environment, south China sea - Run-Xia Sun; Chang-Gui Pan; Feng-Jiao Peng; Zi-Ling Yu; Hai-Yang Shao; Bing-Zhong Yang; Zhong-Biao Chen; Bi-Xian Mai (Environmental Pollution, 2024)

MGDA-assisted plant washing agent for improving the removal of Cd and Cu from farmland soils - Yi Wang; Chen Tu; Yuan Li; Shuai Yang; Ying Liu; Xia Zhu; Shao-cheng Si; Run-lai Luo; Xiang-liang Pan; Yong-ming Luo (Environmental Pollution, 2024)

Exercise Alleviates Fluoride-Induced Learning and Memory Impairment in Mice: Role of miR-206-3p and PREG - Lei Chai; Qiqi Cao; Ke Liu; Run Zhu; Hao Li; Yanghuan Yu; Jixiang Wang; Ruiyan Niu; Ding Zhang; Bo Yang; Mohammad Mehdi Ommati; Zilong Sun (Biological Trace Element Research, 2024)

Effect of Voluntary Wheel Running on Anxiety- and Depression-Like Behaviors in Fluoride-Exposed Mice - Mengjie Qi; Yue Wu; Han Shi; Jie Liu; Run Zhu; Jixiang Wang; Amna Rafique; Bo Yang; Ruiyan Niu; Ding Zhang; Zilong Sun (Biological Trace Element Research, 2024)

Data-driven neural networks for biological wastewater resource recovery: Development and challenges - Run-Ze Xu; Jia-Shun Cao; Jing-Yang Luo; Bing-Jie Ni; Fang Fang; Weijing Liu; Peifang Wang (Journal of Cleaner Production, 2024)

Suppressed testicular macrophage M1 polarization by HDAC5 enforces insensitivity to LPS-elicited blood-testis barrier damage - Hao Li; Yi-Fan Hu; Xin-Run Wang; Kong-Wen Ouyang; Hua Wang; Kai-Wen Wang; Wei Chang; Jin Zhang; Zhi Yuan; Yong-Wei Xiong; Hua-Long Zhu; Lan Yang; et al. (Food and Chemical Toxicology, 2024)

Development and Application of a Mitochondrial Genetically Encoded Voltage Indicator in Narcosis - Run-Zhou Yang; Dian-Dian Wang; Sen-Miao Li; Pei-Pei Liu; Jian-Sheng Kang (Neuroscience Bulletin, 2024)

Experimental Study on Multistage Seismic Damage Process of Bedding Rock Slope: A Case Study of the Xinmo Landslide - Jing-Jing Tian; Tian-Tao Li; Xiang-Jun Pei; Jian Guo; Shou-Dao Wang; Hao Sun; Pei-Zhang Yang; Run-Qiu Huang (Journal of Earth Science, 2024)

Structurally diverse diterpenoids from the seeds of Caesalpinia minax Hance and their bioactivities - Wen-Chao Tu; Lin-Fen Ding; Liu-Dong Song; Yong-Jiao Li; Run-Cheng Yan; Yun Wu; Wei-Yang Feng; Xing-De Wu (Phytochemistry, 2024)

Vibration reduction and efficiency enhancement effects of twisted rudders in submarines under small rudder angle conditions - Di Zhang; Jin-ming Ye; Wan-li Yang; Yuan-run Wu; Jian-lin Shou (Ocean Engineering, 2024)

Ecotoxicological assessment, oxidative response, and enzyme activity disorder of the rotifer Brachionus asplanchnoidis exposed to a toxic cocktail of spent lithium-ion battery leachate - Yi-fan Feng; Yu Zhang; Run-jia Yang; Si-qi Li; Xiao-jie Liu; Cui Han; Yi-fu Xing; Jia-xin Yang (Journal of Hazardous Materials, 2024)

Microplastic-free, single-layered functional surface with localized liquid-discharging molecular channels for disposable hygiene products - Mei Liu; Ruimin Xie; Chi Ma; Jielin Xu; Run Zhao; Lili Deng; Shiyan Chen; Jianping Yang; Liming Zou; Huaping Wang; Jing Wu (Chemical Engineering Journal, 2024)

Immobilization of Nickel- and Cobalt-Based Complexes in NH2-UiO-66 for Efficient CO2 Photoreduction - Yu Jiang; Si-Chao Liu; Li-Ping Zhang; Guo-Wei Guan; Yi-Tao Li; Shuang Ni; Run-Yuan Jiang; Su-Tao Zheng; Hao-Ran Liu; Hao-Ling Lan; Qing-Yuan Yang (Chemical Engineering Journal, 2024)

Occurrence and mechanism of sulfamethoxazole in alginate-like extracellular polymers from excess sludge - Chen Shi; Ming Cheng; Run-Gen Zeng; Cong-Cong Li; Qian Wang; Li-Ting Hao; Ran-Bin Liu; Xiao-Di Hao; Xiang-Yang Wang; Yuan-Yuan Wu (Bioresource Technology, 2024)

Structure and dynamics of microbial communities associated with the resurrection plant Boea hygrometrica in response to drought stress - Run-Ze Sun; Yuan-Yuan Wang; Xiao-Qiang Liu; Zhao-Lin Yang; Xin Deng (Planta, 2024)

Integrative Metabolomics and Whole Transcriptome Sequencing Reveal Role for TREM2 in Metabolism Homeostasis in Alzheimer’s Disease - Meng Wang; Tao Wei; Chaoji Yu; Ruiyang Li; Yunsi Yin; Hanchen Yang; Run Di; Xinyi Xia; Qi Qin; Yi Tang (Molecular Neurobiology, 2024)

MiRNA-seq and mRNA-seq revealed the mechanism of fluoride-induced cauda epididymal injury - Yanghuan Yu; Run Zhu; Mengjie Qi; Jie Liu; Kewei Cao; Ding Zhang; Bo Yang; Ruiyan Niu; Jundong Wang; Yangfei Zhao; Zilong Sun (Science of The Total Environment, 2024)

Overall and geographic pattern of incidence, fatality and mortality of sepsis among hospitalized non-child cancer patients in China: A nationwide cross-sectional study - Bin Lu; Yang Xu; Na Li; Yueyang Zhou; Xudong Ma; Yan Chen; Run Dong; Xiang Zhou; Min Dai; Hongda Chen; Li Weng; Bin Du (Science Bulletin, 2024)

Bi-2-(2-phenethyl)chromone derivatives from agarwood of Aquilaria filaria in the Philippines - Hong-Run Yang; Hao Wang; Pei Wang; Fang-Zheng Liu; Hong-Xing Chai; Cai-Hong Cai; Li Yang; Jing-Zhe Yuan; Bei Jiang; Wen-Li Mei; Hao-Fu Dai (Phytochemistry, 2024)

Research on the equivalent stiffness of bucket foundations for offshore wind power - Huishan Li; Jijian Lian; Run Liu; Haijun Wang; Xu Yang (Ocean Engineering, 2024)

Mixotrophic denitrification of waste activated sludge fermentation liquid as an alternative carbon source for nitrogen removal: Reducing N2O emissions and costs - Fang Fang; Jie Yang; Ling-Long Chen; Run-Ze Xu; Jing-Yang Luo; Bing-Jie Ni; Jia-Shun Cao (Journal of Environmental Management, 2024)

Modified Chinese quince oligomeric proanthocyanidin protects deep-frying oil quality by inhibiting oxidation - Run-Yang Zhang; Wan-Qing Kong; Zhao Qin; Hua-Min Liu; Xue-De Wang (Food Chemistry, 2024)

Fe-N co-doped biochar derived from biomass waste triggers peracetic acid activation for efficient water decontamination - Ruyan Ning; Yudan Dong; Shu-Run Yang; Shuai Yang; Peng Zhou; Zhaokun Xiong; Zhi-Cheng Pan; Chuan-Shu He; Bo Lai (Journal of Hazardous Materials, 2024)

Preparing a heavy-metal adsorbent based on alginate-like extracellular polymers from conventional activated sludge via polyethyleneimine grafting - Chen Shi; Run-Gen Zeng; Shi-Chao Yuan; Lin Zhang; Xiang-Yang Wang; Li-Ting Hao; Xiao-Di Hao; Nan Zhang; Yuan-Yuan Wu (Sustainable Chemistry and Pharmacy, 2024)

Indole-3-acetic acid improves periphyton's resistance to ultraviolet-B: From physiological-biochemical properties and bacteria community to livestock-polluted water purification - Tianyu Shi; Maobulin Lure; Run Zhang; Zhiheng Liu; Qianming Hu; Jia Liu; Shengtao Yang; Liandong Jing (Environmental Research, 2024)

Biomimetic hierarchical composites inspired by natural pomelo peel for mechanical-damage resistance and storage of fruits - Run-Ze Hu; Lei Liu; En-Jiang Liu; Jie Tu; Xiao-Hui Yao; Peng Song; Dong-Yang Zhang; Zhan-Hua Huang; Tao Chen (Chemical Engineering Journal, 2024)

Analysis of stakeholder-associated factors and their interactions in energy conservation behaviour of occupants: evidence from network analysis - Yin-Run Yang; Jian Zuo; Min Pan; Rui-Dong Chang; Zhuo-Jing Zou; Ronald J. Webber; Na Dong (Environment, Development and Sustainability, 2024)

A near-infrared fluorescent probe for rapid and on-site detection of sulfur dioxide derivative in biological, food and environmental systems - Zhuye Shang; Miaomiao Wu; Qingtao Meng; Yang Jiao; Zhiqiang Zhang; Run Zhang (Journal of Hazardous Materials, 2024)

3D microprinting of QR-code integrated hydrogel tactile sensor for real-time E-healthcare - Zi-Rong Li; Tian-Run Lv; Zhenxu Yang; Wen-Hai Zhang; Ming-Jie Yin; Ken-Tye Yong; Quan-Fu An (Chemical Engineering Journal, 2024)

Transcriptomic analysis of ncRNAs and mRNAs interactions during drought stress in switchgrass - Cong Guan; Wei Li; Guoliang Wang; Ruimei Yang; Jinglei Zhang; Jinhong Zhang; Bo Wu; Run Gao; Chunlin Jia (Plant Science, 2024)

Episodic water-fluxed anatexis recorded by migmatites from the Paleozoic Wuyi-Yunkai Orogeny in South China - Er-Kun Xue; Wei Wang; David Chew; Manoj K. Pandit; Xin Deng; Yang Tian; Xi-Run Tong; Jun-Hong Zhao (Gondwana Research, 2024)

Spatial-temporal variation of soil organic matter decomposition potential in China - Qi Chen; Zeyan Zhou; Sulin Cai; Meiqi Lv; Yinghui Yang; Yunchao Luo; Han Jiang; Run Liu; Tingting Cao; Bei Yao; Yunru Chen; Qiang Li; et al. (Soil and Tillage Research, 2024)

Response of grassland growing season length to extreme climatic events on the Qinghai-Tibetan Plateau - Run Zhong; Kai Yan; Si Gao; Kai Yang; Shuang Zhao; Xuanlong Ma; Peng Zhu; Lei Fan; Gaofei Yin (Science of The Total Environment, 2024)

Fluctuations of Qiangyong glacier in southern Tibetan Plateau over the past 500 years recorded by proglacial lacustrine sediments - Run Zhang; Qi Feng; Fei Zhang; Le Li; Yang Xu; Zhangdong Jin (Quaternary International, 2024)

Outdoor artificial light at night and male sperm quality: A retrospective cohort study in China - Run Tian; Tingting Yang; Chenghan Xiao; Fuping Li; Leyao Fu; Lu Zhang; Jiarui Cai; Sixuan Zeng; Junhao Liao; Guishuang Song; Chuan Yu; Ben Zhang; et al. (Environmental Pollution, 2024)

Green N1 additive modified perovskite precursor enables effective manufacturing of large-area solar cell modules with high efficiency and stability - Yue Zang; Yibo Tu; Chuanjia Jiao; Wangnan Li; Peng Zhou; Jiahao Cheng; Gaoyuan Yang; Tianxiang Shao; Jingchuan Ye; Guodong Li; Liang Chu; Shaojian Lu; et al. (Chemical Engineering Journal, 2024)

Effects of Ulva prolifera Degradation on Growth Performance and Antioxidant Capacity of Japanese Flounder (Paralichthys olivaceus) Family - Yingming Yang; Wenlong Li; Run Wang; Dan Xu; Yadong Chen; Zhongkai Cui; Songlin Chen (Fishes, 2023)
Massive macroalgae blooms, primarily caused by the overgrowth of Ulva prolifera (U. prolifera) in the Yellow Sea of China, pose a severe risk to both marine organisms and the aquaculture industry. This study’s aim was to evaluate the impact of U. prolifera degradation on the growth performance and antioxidant capacity of Japanese flounder (Paralichthys olivaceus) and select some potential Japanese flounder families (labeled 2101–2108, established by crossbreeding) tolerating U. prolifera degradation conditions. Thus, a 60-day U. prolifera exposure experiment was conducted. The results showed that the contents of Na, K, Mg, and Fe elements in the U. prolifera degradation water were significantly increased. The specific growth rate and survival rate of flounder were significantly decreased under the U. prolifera degradation condition, while the 2101 and 2103 flounder families showed a better growth performance compared with the positive control (PC) group. Moreover, the results showed that activities of total antioxidant capacity (T-AOC), transaminases, and alkaline phosphatase (AKP) in serum were significantly decreased, while the 2103 flounder family showed higher activities. Furthermore, U. prolifera degradation significantly increased superoxide dismutase (SOD) activity and glutathione (GSH) content while decreasing catalase (CAT) activity and malondialdehyde (MDA) content in the liver. Specifically, SOD and CAT activities of the 2103 flounder family were higher than the 2101 flounder family and PC group. In addition, the gill SOD and CAT activities of the 2103 flounder family were significantly higher than the PC group. Similarly, the antioxidant-related gene (sod and cat) expressions were synchronously upregulated or downregulated in the liver and gills in response to U. prolifera degradation. These results revealed that U. prolifera degradation decreased the growth performance and influenced the antioxidant capacity of Japanese flounder, while the 2103 flounder family had better advantages in the U. prolifera degradation condition. Therefore, the 2103 flounder family could be regarded as the potential flounder family tolerating U. prolifera degradation. The increased Fe content in the U. prolifera degradation water may be one of the main causes of the physiological alterations observed in Japanese flounder.

Graphene oxide composited with different size of organic molecules for hydrogen isotopic water separation in membrane distillation - Run Li; Denggao Guan; Min Chen; Xin Zhang; Haowei Yang; Cigang Xu (Journal of Environmental Chemical Engineering, 2023)

A novel non-centrifugal sugar prepared from tiger nut (Cyperus esculentus L.) meal: Preparation methods and comparison with sugarcane - Run-Yang Zhang; Xin-Yun Huang; Peng-Xiao Chen; Tian Li; Meng-Meng Jiang; Yi-Long Wang; Wen-Xue Zhu; Hua-Min Liu (Food Research International, 2023)

Soil aggregate-associated organic carbon mineralization and its driving factors in rhizosphere soil - Jun-Ya Li; Peng Chen; Zhi-Guo Li; Lin-Yang Li; Run-Qin Zhang; Wei Hu; Yi Liu (Soil Biology and Biochemistry, 2023)

Phosphorus recovery from synthetic anaerobic fermentation supernatant via vivianite crystallization: Coupling effects of various physicochemical process parameters - Jia-Shun Cao; Su-Na Wang; Run-Ze Xu; Jing-Yang Luo; Bing-Jie Ni; Fang Fang (Science of The Total Environment, 2023)

Biomethane is produced by acetate cleavage, not direct interspecies electron transfer: genome-centric view and carbon isotope - Jian Liu; Jiafeng Yu; Yang Tan; Run Dang; Meng Zhou; Marcela Hernández; Eric Lichtfouse; Leilei Xiao (Bioresource Technology, 2023)

Integrated MOVES model and machine learning method for prediction of CO2 and NO from light-duty gasoline vehicle - Run Liu; Hong-di He; Zhe Zhang; Cui-lin Wu; Jin-ming Yang; Xing-hang Zhu; Zhong-ren Peng (Journal of Cleaner Production, 2023)

Suppression effects and mechanisms of three typical solid suppressants on titanium hydride dust explosions - Shi-zhou Li; Yang-fan Cheng; Rui Wang; Meng Li; Run Li; Hong-hao Ma (Process Safety and Environmental Protection, 2023)

Lateral bearing capacity and calculation method of pile-bucket foundation in clay for offshore wind turbines - Run Liu; Jieyang Shi; Guangsi Chen; Xu Yang (Ocean Engineering, 2023)

Examining the impacts of implicit economic policy on urban environmental pollution: Unveiling pathways for sustainable recovery - Ya Yang; Mengru Zhou; Yawei Hou; Run Tang; Bo Liu; Yue Deng (Resources Policy, 2023)

A new butenolide with antifungal activity from solid co-cultivation of Irpex lacteus and Nigrospora oryzae - Ya-Mei Wu; Xue-Qiong Yang; Jing-Xin Chen; Ting Wang; Tai-Ran Li; Fan-Rong Liao; Run-Tong Liu; Ya-Bin Yang; Zhong-Tao Ding (Natural Product Research, 2023)

Effect of polylactic acid microplastics on soil properties, soil microbials and plant growth - Run Liu; Jiawen Liang; Yinghui Yang; Han Jiang; Xingjun Tian (Chemosphere, 2023)

Antimicrobial resistome during the transition from an integrated to a monoculture aquaculture farm in southern China - Jin-Tao Yang; Dan-Yu Xiao; Li-Juan Zhang; Hai-Xin Chen; Xing-Run Zheng; Xiao-Li Xu; Hong-Xia Jiang (Science of The Total Environment, 2023)

Review of characteristics, generation pathways and detection methods of singlet oxygen generated in advanced oxidation processes (AOPs) - Zhi-Hui Xie; Chuan-Shu He; Dan-Ni Pei; Yudan Dong; Shu-Run Yang; Zhaokun Xiong; Peng Zhou; Zhi-Cheng Pan; Gang Yao; Bo Lai (Chemical Engineering Journal, 2023)

Characteristics of spatial and temporal carbon emissions from different land uses in Shanxi section of the Yellow River, China - Lin Zhao; Meng-na Chen; Chuan-hao Yang; Run-ze Zhang; Qi-peng Zhang; Qian Wang (Environment, Development and Sustainability, 2023)

Overexpression of OsNF-YB4 leads to flowering early, improving photosynthesis and better grain yield in hybrid rice - Meifang Peng; Feng Gan; Xiaomin Lin; Run Yang; Shaoyi Li; Wei Li; Lan Wu; Xiaoli Fan; Kegui Chen (Plant Science, 2023)

Porous ceramic membranes from coal fly ash with addition of various pore-forming agents for oil-in-water emulsion separation - Jiguang Huang; Haiping Chen; Run Qi; Jihao Yang; Zhaohao Li; Heng Zhang (Journal of Environmental Chemical Engineering, 2023)

Dynamic response and failure analysis for urban bridges under far-field blast loads - Shanglin Yang; Zhicheng Liu; Shufei Wang; Wei Zhong; Run Zhang; Xiaohu Yao (Engineering Structures, 2023)

Peracetic acid activation via the synergic effect of Co and Fe in CoFe-LDH for efficient degradation of pharmaceuticals in hospital wastewater - Zhi-Hui Xie; Chuan-Shu He; Yong-Li He; Shu-Run Yang; Si-Ying Yu; Zhaokun Xiong; Ye Du; Yang Liu; Zhi-Cheng Pan; Gang Yao; Bo Lai (Water Research, 2023)

Eliminating temporal correlation in quantum-dot entangled photon source by quantum interference - Run-Ze Liu; Yu-Kun Qiao; Han-Sen Zhong; Zhen-Xuan Ge; Hui Wang; Tung-Hsun Chung; Chao-Yang Lu; Yong-Heng Huo; Jian-Wei Pan (Science Bulletin, 2023)

Facile, green and scalable preparation of low-cost PET-PVDF felts for oil absorption and oil/water separation - Ming Hao; Tianyi Zhang; Xiaodong Hu; Zhijun Chen; Bo Yang; Xiaoxiao Wang; Yanbo Liu; Run Wang; Yong Liu (Journal of Hazardous Materials, 2023)

Variations in the concentration, source and flux of polycyclic aromatic hydrocarbons in sediments of the Pearl River Estuary: Implications for anthropogenic impacts - Yali Li; Nairong Guo; Ke Yuan; Baowei Chen; Junjie Wang; Maofeng Hua; Jing Yu; Jingyan Hu; Run Lu; Shichun Zou; Ying Yang (Science of The Total Environment, 2023)

Metabolomics and lipidomics profiles related to intramuscular fat content and flavor precursors between Laiwu and Yorkshire pigs - Xinhua Hou; Run Zhang; Man Yang; Naiqi Niu; Junchao Wu; Ze Shu; Pengfei Zhang; Lijun Shi; Fuping Zhao; Ligang Wang; Lixian Wang; Longchao Zhang (Food Chemistry, 2023)

Research for the recovery of Zn and Pb from electric arc furnace dust through vacuum carbothermal reduction - Jing Yang; Run Huang; Xuan He; Xiaodong Lv; Renlin Zhu; Huixin Jin; Xue Deng (Process Safety and Environmental Protection, 2023)

Seasonal spermatogenesis, epididymal storage, and creatine kinase expression in Pelodiscus sinensis - Yu-Fei Yang; Jia-Hao Wu; Run-Lan Lin; Shang-Jun Yin; Guo-Ying Qian; Wei Wang; Yong-Doo Park (Animal Reproduction Science, 2023)

Urinary trihalomethane concentrations and liver function indicators: a cross-sectional study in China - Li Yang; Limei Chen; Yamei Hao; Run Zhou; Jingying Zhu; Xun Zhu; Qianqian Wang; Xiuzhu Li; Xinliang Ding; Yanhua Qian (Environmental Science and Pollution Research, 2023)

Non-destructive characterization of proton diffusion coefficient within live electroactive biofilm - Linbin Hu; Run Liu; Yang Yang; Qian Fu; Liang Zhang; Xun Zhu; Qiang Liao; Jun Li (Chemical Engineering Journal, 2023)

The local ecological knowledge of butterfly diversity is derived from utilitarian purposes in Southwest China’s biodiversity hotspot - Run-Ming Yang; Shao-Ji Hu; Benjamin D. Blanchard; Akihiro Nakamura (Biodiversity and Conservation, 2022)

PLC1 and H2O2 Mediated the Allelopathic Effect of Oridonin on Root Growth in Arabidopsis thaliana - Yue Zhang; Yanhuang An; Ning Yang; Wei Wang; Ruirui Liu; Run Gao; Yaping Zhou (Journal of Plant Growth Regulation, 2022)

Cardiac inflammation and fibrosis following chemo/radiation therapy: mechanisms and therapeutic agents - Run Yang; Changming Tan; Masoud Najafi (Inflammopharmacology, 2022)

A numerical method of combined SPF-MEM-LBM on the rockfall-induced surge and its application - Qiu-jie Meng; Yi-xiang Song; Da Huang; Run-qiu Huang; Zhu Zhong; Wen-bo Huang; Yang Liu (Journal of Mountain Science, 2022)

Different Changing Patterns of Three NOS–NO System Activities after Ischemia–Reperfusion in Rabbit with AMI - Jun Zhang; Chao Chen; Fengpeng Li; Guangren Gao; Jinguo Fu; Heping Niu; Kai Yu; Lei Wang; Run Guo; Yanfang Wan; Zhanfeng Ma; Qianyu Zhang; et al. (Cell Biochemistry and Biophysics, 2021)

Exploring the dynamic mechanism of allosteric drug SHP099 inhibiting SHP2E69K - Shan Du; Xin-hua Lu; Wei-Ya Li; Li-Peng Li; Yang-Chun Ma; Liang Zhou; Jing-Wei Wu; Ying Ma; Run-Ling Wang (Molecular Diversity, 2021)

High-throughput sequencing reveals the molecular mechanisms determining the stay-green characteristic in soybeans - Cheng Wang; Le Gao; Run Zhi Li; Ye Wang; Yang Ying Liu; Xin Zhang; Hao Xie (Journal of Biosciences, 2020)

Deformation and failure of a high-steep slope induced by multi-layer coal mining - Jian-le Yu; Jian-jun Zhao; Hao-yuan Yan; Qi-yi Lai; Run-qiu Huang; Xiu-wei Liu; Yang-chnn Li (Journal of Mountain Science, 2020)

Suppression of miR-30a-3p Attenuates Hepatic Steatosis in Non-alcoholic Fatty Liver Disease - De-Run Wang; Bing Wang; Ming Yang; Zhen-lu Liu; Jing Sun; Yan Wang; Hui Sun; Liang-Jun Xie (Biochemical Genetics, 2020)

Characterization of a Cu2+, SDS, alcohol and glucose tolerant GH1 β-glucosidase from Bacillus sp. CGMCC 1.16541 - Yi-Rui Yin; Peng Sang; Feng-Li Yang; Tao Li; Run-Feng Yang; Hong-Yan Liu; Zong-Long Luo; Wen-Jun Li; Li-Quan Yang (Antonie van Leeuwenhoek, 2020)

Physical Model Experimental Study on Spalling Failure Around a Tunnel in Synthetic Marble - Guo-Qiang Zhu; Xia-Ting Feng; Yang-Yi Zhou; Zheng-Wei Li; Lian-Jie Fu; Yong-Run Xiong (Rock Mechanics and Rock Engineering, 2020)

A role of age-dependent DNA methylation reprogramming in regulating the regeneration capacity of Boea hygrometrica leaves - Run-Ze Sun; En-Hui Zuo; Jin-Feng Qi; Yang Liu; Chih-Ta Lin; Xin Deng (Functional & Integrative Genomics, 2020)

Isolation and synthesis of a new benzylated alkamide from the roots of Lepidium meyenii - Yan-Qing Ye; Zu-Hong Ma; Qiao-Fen Yang; Yan-Qi Sun; Rui-Qi Zhang; Run-Fang Wu; Xin Ren; Li-Juan Mu; Zhi-Yong Jiang; Min Zhou (Natural Product Research, 2019)

Impact of polymer mixtures on the stabilization and erosion control of silty sand slope - Qing-wen Yang; Xiang-jun Pei; Run-qiu Huang (Journal of Mountain Science, 2019)

DNMT3A controls miR-200b in cardiac fibroblast autophagy and cardiac fibrosis - Xu-Dong Zhao; Run-He Qin; Jing-Jing Yang; Sheng-Song Xu; Hui Tao; Xuan-Sheng Ding; Kai-Hu Shi (Inflammation Research, 2018)

Selective precipitation and characterization of lignin–carbohydrate complexes (LCCs) from Eucalyptus - Bao-Cheng Zhao; Ji-Dong Xu; Bo-Yang Chen; Xue-Fei Cao; Tong-Qi Yuan; Shuang-Fei Wang; Adam Charlton; Run-Cang Sun (Planta, 2018)

Identification and mapping of ts (tender spines), a gene involved in soft spine development in Cucumis sativus - Chunli Guo; Xuqin Yang; Yunli Wang; Jingtao Nie; Yi Yang; Jingxian Sun; Hui Du; Wenying Zhu; Jian Pan; Yue Chen; Duo Lv; Huanle He; et al. (Theoretical and Applied Genetics, 2018)

Kitamycin C, a new antimycin-type antibiotic from Streptomyces antibioticus strain 200-09 - Fan Wang; Shu-Na Fu; Yi-Xuan Bao; Yu Yang; Hui-Fang Shen; Bi-Run Lin; Guang-Xiong Zhou (Natural Product Research, 2017)

Accumulation of freshwater in the permanent ice zone of the Canada Basin during summer 2008 - Jinlu Tong; Min Chen; Weifeng Yang; Run Zhang; Hong Pan; Minfang Zheng; Yusheng Qiu; Wangjiang Hu; Jian Zeng (Acta Oceanologica Sinica, 2017)

The In vitro/vivo Evaluation of Prepared Gastric Floating Tablets of Berberine Hydrochloride - Jun Ji; Xin He; Xiao-Lin Yang; Wen-Juan Du; Cheng-Long Cui; Ling Wang; Xue Wang; Chun-Feng Zhang; Chang-Run Guo (AAPS PharmSciTech, 2017)

Inhibitory effect of estrogen receptor beta on P2X3 receptors during inflammation in rats - Qian Jiang; Wen-xin Li; Jia-run Sun; Tian-tian Zhu; Juan Fan; Li-hua Yu; Geoffrey Burnstock; Hua Yang; Bei Ma (Purinergic Signalling, 2017)

Skarn mineralogy and its geological significance for the Tayuan (Cu–Mo)–Pb–Zn deposit, northern Daxinganling metallogenic belt - Chao Li; Tao Ren; Jian-Guo Huang; Run-Sheng Han; He-Jun Yin; Hong-Yang Zhou; Zhi-Hong Feng (Acta Geochimica, 2017)

Phylogeography of Achyranthes bidentata (Amaranthaceae) in China’s Warm-Temperate Zone Inferred from Chloroplast and Nuclear DNA: Insights into Population Dynamics in Response to Climate Change During the Pleistocene - Cai-Yun Miao; Jie Yang; Run-Li Mao; Yong Li (Plant Molecular Biology Reporter, 2017)

XCI-escaping gene KDM5C contributes to ovarian development via downregulating miR-320a - Yi-Xi Sun; Yi-Xin Zhang; Dan Zhang; Chen-Ming Xu; Song-Chang Chen; Jun-Yu Zhang; Ye-Chun Ruan; Feng Chen; Run-Ju Zhang; Ye-Qing Qian; Yi-Feng Liu; Lu-Yang Jin; et al. (Human Genetics, 2017)

A Brachypodium distachyon MAPKK Gene BdMKK6.2 Negatively Regulates Drought Stress Tolerance in Transgenic Tobacco Plants - Jiutong Sun; Run Zhou; Yaping Li; Wei Hu; Ding Qiu; Xiatian Wang; Qiong Wang; Zhijuan Feng; Lianzhe Wang; Yi Zhou; Guangyuan He; Guangxiao Yang (Journal of Plant Growth Regulation, 2016)

The Synergic Relationship Between Xylan Removal and Enhanced Cellulose Digestibility for Bioethanol Production: Reactive Area, Crystallinity, and Inhibitation - Haiyan Yang; Jinghuan Chen; Qian Chen; Kun Wang; Run-Cang Sun (BioEnergy Research, 2015)

A Real-time monitoring and early warning system for landslides in Southwest China - Neng-pan Ju; Jian Huang; Run-qiu Huang; Chao-yang He; Yan-rong Li (Journal of Mountain Science, 2015)

Physical‐biological coupling of N 2 fixation in the northwestern S outh C hina S ea coastal upwelling during summer - Run Zhang; Min Chen; Qing Yang; Yuanshao Lin; Huabin Mao; Yusheng Qiu; Jinlu Tong; E. Lv; Zhi Yang; Weifeng Yang; Jianping Cao (Limnology and Oceanography, 2015)
Here, we present the first combined results of N 2 fixation rates ( 15 N 2 assay), dissolved iron (dFe, 14 C assay) in the northwestern South China Sea (NWSCS) coastal upwelling region during summer. Surface N 2 fixation rate ranged between 0.1 nmol N L −1 d −1 and 5.6 nmol N L −1 d −1 (average 1.0 nmol N L −1 d −1 , n = 50) under nonbloom conditions. At a Trichodesmium bloom station, N 2 fixation rate was ∼ 3 orders of magnitude higher. Depth‐integrated N 2 fixation rate ranged between 7.5 μmol N m −2 d −1 and 163.1 μmol N m −2 d −1 (average 46.4 μmol N m −2 d −1 ). Our results indicate that N 2 fixation is unlikely limited by Fe availability in the NWSCS continental waters, instead, the coastal upwelling‐induced combined effects of physical and biological processes may have played a decisive role. With the upwelled cold, dFe‐rich, nutrient‐replete waters, nondiazotrophic phytoplankton growth would be preferentially enhanced while N 2 fixation was hindered due to relative deficiency of phosphate caused by massive phytoplankton utilization in the coastal upwelling. By comparison, N 2 fixation was notably elevated along with decreased PP in the offshore waters, probably due to a shift from P‐deficiency to N‐deficiency. Consistently, the contribution of N 2 fixation to PP (0.01–2.52%) also increased toward the open waters. As a significant external N source, summertime N 2 fixation is estimated to contribute a flux of 1.4 Gmol N to this area under nonbloom conditions. This study adds to the knowledge of N 2 fixation in the rarely studied subtropical coastal upwellings, and highlights the necessity of future comprehensive studies in such highly dynamic environments.

The Brachypodium distachyon BdWRKY36 gene confers tolerance to drought stress in transgenic tobacco plants - Jiutong Sun; Wei Hu; Run Zhou; Lianzhe Wang; Xiatian Wang; Qiong Wang; Zhijuan Feng; Yaping Li; Ding Qiu; Guangyuan He; Guangxiao Yang (Plant Cell Reports, 2015)

Evolution of High-Affinity Peptide Probes to Detect the SH3 Domain of Cancer Biomarker BCR–ABL - Hui-Min Liu; Li-Juan Li; Juan Guo; Zhan-Jia Yang; Xiao Yang; Run-Peng Qi; Wei Cao (International Journal of Peptide Research and Therapeutics, 2014)

Low 210Pb in the upper thermocline in the Canadian Basin: scavenge process over the Chukchi Sea - Wangjiang Hu; Min Chen; Weifeng Yang; Run Zhang; Yusheng Qiu; Minfang Zheng (Acta Oceanologica Sinica, 2014)

Fine mapping of the uniform immature fruit color gene u in cucumber (Cucumis sativus L.) - Xuqin Yang; Yue Li; Weiwei Zhang; Huanle He; Junsong Pan; Run Cai (Euphytica, 2014)

Phenotypic and genetic parameter estimation of morphological traits related to axial body growth in Japanese flounder - Yong-Xin Liu; Li Jiang; Hai-Jin Liu; Run-Qing Yang (Fisheries Science, 2014)

Expression of yeast acyl-CoA-∆9 desaturase leads to accumulation of unusual monounsaturated fatty acids in soybean seeds - Jin-Ai Xue; Xue Mao; Zhi-Rong Yang; Yong-Mei Wu; Xiao-Yun Jia; Li Zhang; Ai-Qin Yue; Ji-Ping Wang; Run-Zhi Li (Biotechnology Letters, 2013)

Effect of the CYP2C19*2 and *3 genotypes, ABCB1 C3435T and PON1 Q192R alleles on the pharmacodynamics and adverse clinical events of clopidogrel in Chinese people after percutaneous coronary intervention - Xiao-Fang Tang; Jing Wang; Jia-Hui Zhang; Xian-Min Meng; Bo Xu; Shu-Bin Qiao; Yong-Jian Wu; Jue Chen; Yuan Wu; Ji-Lin Chen; Run-Lin Gao; Jin-Qing Yuan; et al. (European Journal of Clinical Pharmacology, 2013)

RT-PCR test for detecting porcine sapovirus in weanling piglets in Hunan Province, China - Guo-Hua Liu; Run-Cheng Li; Ze-Bin Huang; Jun Yang; Chao-Ting Xiao; Jing Li; Man-Xiang Li; Yun-Qiu Yan; Xing-Long Yu (Tropical Animal Health and Production, 2012)

The 223A>G polymorphism of the leptin receptor gene is associated with macroangiopathy in type 2 diabetes mellitus - Run-tao Gan; Shu-sen Yang (Molecular Biology Reports, 2012)

Effects of temporarily disrupting BBB on activity-induced manganese-dependent functional MRI - Zhiqiang Fa; Run Zhang; Peng Li; Jing Zhang; Peng Zhang; Shaofang Zhu; Qu Wu; Fanheng Huang; Yanping Liu; Lujun Yang; Haigang Chang; Zhibo Wen; et al. (Brain Imaging and Behavior, 2011)

Comparative ecophysiological responses to drought of two shrub and four tree species from karst habitats of southwestern China - Chang-Cheng Liu; Yu-Guo Liu; Ke Guo; Guo-Qing Li; Yuan-Run Zheng; Li-Fei Yu; Rui Yang (Trees, 2011)

Screening Level of PAHs in Sediment Core from Lake Hongfeng, Southwest China - Jian-Yang Guo; Feng-Chang Wu; Liang Zhang; Hai-Qing Liao; Run-Yu Zhang; Wei Li; Xiao-Li Zhao; She-Jun Chen; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2011)

RRM1 gene expression in peripheral blood is predictive of shorter survival in Chinese patients with advanced non-small-cell lung cancer treated by gemcitabine and platinum - Lin-run Wang; Guo-bing Zhang; Jian Chen; Jun Li; Ming-wei Li; Nong Xu; Yang Wang; Jian-zhong Shen Tu (Journal of Zhejiang University-SCIENCE B, 2011)

The Cucumber Lateral Suppressor Gene (CLS) Is Functionally Associated with Axillary Meristem Initiation - Li-Hua Yuan; Jun-Song Pan; Gang Wang; Jun Zhu; Wei-Wei Zhang; Zheng Li; Huan-Le He; Zhong-Nan Yang; Run Cai; Li-Huang Zhu (Plant Molecular Biology Reporter, 2010)

Inhibiting effect of vagal nerve stimulation to seizures in epileptic process of rats - Hong-Jun Yang; Kai-Run Peng; San-Jue Hu; Yan Liu (Neuroscience Bulletin, 2007)

Characterizations of a Hypomorphic Argonaute1 Mutant Reveal Novel AGO1 Functions in Arabidopsis Lateral Organ Development - Li Yang; Weihua Huang; Hua Wang; Run Cai; Yuquan Xu; Hai Huang (Plant Molecular Biology, 2006)